Racial differences in central adiposity in a longitudinal cohort of black and white adolescent females - Daniels Stephen R; Dallal Gerard E; Lichtenstein Alice H; Tybor David J; Must Aviva (BMC, 2010)
Abstract Background Central adiposity is related to chronic disease risk in adolescents. Racial differences in waist circumference have been identified using cross-sectional data from this age group. We tested for racial differences in age-related growth in waist circumference in a longitudinal cohort of black and white adolescent girls. Methods We analyzed 9 years of publicly available data from the National Heart, Lung, and Blood Institute Growth and Health Study, for 2379 girls (1213 black and 1166 white) enrolled at age 9-10 years in 1987-1988 and followed annually. Individual growth trajectories of waist circumference were constructed for girls with >3 annual measures. Mixed models were used to compare changes in waist circumference during adolescence between black and white females. BMI and age at menarche were included in the models. Results At each age, black females had significantly higher waist circumference. Mean annual increase in waist circumference was significantly higher for black females compared to white females (1.46 cm/yr vs. 1.36 cm/yr, respectively). After adjusting for BMI, the mean annual increase in waist circumference for white females was significantly higher than for black females (0.08 cm/yr vs. -0.07 cm/yr, respectively). These relationships remained significant after adjusting for age at menarche. Conclusions Black females had significantly steeper increases in waist circumference over adolescence than white females. After adjusting for BMI and age at menarche, however, the annual increase in waist circumference for black females was significantly shallower than for their white peers. These data suggest racial differences in the deposition of fat over the adolescent period.